An Integrated Critical Path Method and PERT Approach for Schedule Performance Evaluation of Drainage Construction Projects - Ilham; Habir; Tukimun (Indonesia Academia Research Society, 2025)
Time control is a critical factor in the successful delivery of drainage construction projects, which are often characterized by high complexity, limited working space, and significant uncertainty in activity durations. Delays in such projects can have substantial economic and social impacts, underscoring the need for reliable schedule performance evaluation. This study aims to evaluate the schedule performance of a drainage construction project by integrating the Critical Path Method (CPM) and the Program Evaluation and Review Technique (PERT) using a Work Breakdown Structure (WBS)-based approach. The research employs secondary data in the form of a project schedule presented as a weekly S-curve with a planned duration of 180 calendar days. A CPM network is developed at the WBS level to identify the dominant project path, followed by applying PERT to critical activities to assess duration uncertainty and completion probability. The results indicate that the dominant path consists of preparation works, earthworks and piling works, drainage channel construction, and pedestrian access works, with drainage channel construction identified as the most critical activity. The PERT analysis reveals that uncertainty in dominant activities increases the expected project duration and reduces the likelihood of on-time completion. These findings suggest that deterministic scheduling alone may underestimate project timelines, whereas integrating CPM and PERT provides a more realistic evaluation framework. The study concludes that a WBS-based CPM–PERT approach is effective for assessing schedule performance under data limitations and offers practical insights for improving project time control and decision-making.